2014
DOI: 10.3389/fnhum.2014.00503
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude differences in high-frequency fMRI signals between eyes open and eyes closed resting states

Abstract: Recent studies employing rapid sampling techniques have demonstrated that the resting state fMRI (rs-fMRI) signal exhibits synchronized activities at frequencies much higher than the conventional frequency range (<0.1 Hz). However, little work has investigated the changes in the high-frequency fluctuations between different resting states. Here, we acquired rs-fMRI data at a high sampling rate (TR = 400 ms) from subjects with both eyes open (EO) and eyes closed (EC), and compared the amplitude of fluctuation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 42 publications
12
68
0
Order By: Relevance
“…In addition, we observed higher long-term reliability of CBF-ALFF in the lateral prefrontal cortex in the EO state, which might be induced by larger inter-subject difference in neuronal activity or by artifacts resulting from eye movement such as blinks. An shown in a previous study, the amplitude of high-frequency (N 0.1 Hz) fluctuation in the lateral prefrontal cortex was higher in the EO state (Yuan et al, 2014). The temporal resolution of CBF time series was restricted to the low-frequency range (b0.1 Hz).…”
Section: Test-retest Reliability Of Eyes-open and Eyes-closed Statesmentioning
confidence: 57%
See 3 more Smart Citations
“…In addition, we observed higher long-term reliability of CBF-ALFF in the lateral prefrontal cortex in the EO state, which might be induced by larger inter-subject difference in neuronal activity or by artifacts resulting from eye movement such as blinks. An shown in a previous study, the amplitude of high-frequency (N 0.1 Hz) fluctuation in the lateral prefrontal cortex was higher in the EO state (Yuan et al, 2014). The temporal resolution of CBF time series was restricted to the low-frequency range (b0.1 Hz).…”
Section: Test-retest Reliability Of Eyes-open and Eyes-closed Statesmentioning
confidence: 57%
“…Taglizucchi and colleagues showed that instructing subjects to keep their eyes open with/without fixation during the experiment resulted in a decreased amount of sleep than eyes closed (Tagliazucchi and Laufs, 2014 It would be relatively difficult to ask patients to maintain their gaze on a fixation for quite a few minutes. As did in some previous studies (Liu et al, 2013;Yang et al, 2007;Yuan et al, 2014;Zou et al, 2009;Zou et al, 2015), the current study also only focused on the comparisons of the eyes closed state and eyes open without fixation state and hopefully this study would be more helpful to clinical studies. Future comprehensive test-retest reliability studies including EC and EO with/without fixation are warranted.…”
Section: Test-retest Reliability Of Eyes-open and Eyes-closed Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike this study, those studies were interested in local differences so justifiably discarded the mean of each R-fMRI metric with each conditions through performing statistical parametric mapping using the general linear model (Bianciardi et al, 2009;Brandt, 2006;Gonzalez-Hernandez et al, 2005;Marx et al, 2004;Qin et al, 2012;Riedl et al, 2014;Wicker et al, 2003), performing global signal regression to find local significance (Xu et al, 2014;Yuan et al, 2014;Zou et al, 2009), or using paired T-tests on a per voxel basis (which can hypothetically detect a global change if region-to-region variation is small, but will not necessarily as it only compares per-voxel changes and global means are never calculated) (Patriat et al, 2013). All of these methods will amplify local region to region, voxel to voxel variation, but obscure the relations to the global change observed in FDG (Fig.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%